Economies of Scale: Some Statistical Evidence: Comment - Schuman, S. C.; Alpert, S. B. (Quarterly Journal of Economics, 1960)
Journal Article Economies of Scale: Some Statistical Evidence: Comment Get access S. C. Schuman, S. C. Schuman New York, New York Search for other works by this author on: Oxford Academic Google Scholar S. B. Alpert S. B. Alpert New York, New York Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 74, Issue 3, August 1960, Pages 493–497, https://doi.org/10.2307/1883063 Published: 01 August 1960